Análisis de requerimientos y diseño de un sistema web para los procesos administrativos del Subcentro de Salud de la Parroquia Caracol del Cantón Babahoyo - Muñoz Vera, Alexandra Elizabeth (2020)
The present study consists of the analysis of requirements and design of a web system for the administrative processes of the health sub-center of the Parroquia Caracol, its main purpose is to solve the present needs in the mentioned entity. For the collection of information, two methodologies were used, the field and the qualitative, which allowed the application of an interview, where it was stated that one of the main present drawbacks is the lack of organization of the information of the patients, which It is managed in folders, in the same way it was possible to obtain key information to determine the functional and non-functional requirements, which serve as a basis in conjunction with the UML diagrams for the design of the system.